Critical Discourse Analysis of the Suicide Bombings at Three Churches in Surabaya on the News Published by Vice.Com - Rosalina Bilqisth; Rachmat Kriyantono; Anang Sujoko (International Journal of Science and Society, 2021)
This study aims to reveal vice.com's discourse strategy in reporting the suicide bombings at three churches in Surabaya on 13 May 2018. This action caused many victims, namely 28 people died and 57 people were injured. The presence of mass media facilitates the search and acquisition of information by the public, especially with the emergence of online media. People tend to actively find out about what is going on and the existence of online media makes news very easily accessible to the public. Fairclough's critical discourse analysis model is applied to analyze news on vice.com media. Vice.com is an online media based in America-Canada. Vice.com first expanded to Southeast Asia and stopped in Indonesia. This study seeks to examine three levels of analysis in critical discourse analysis, namely: text, discourse practice, and sociocultural practice. Vice.com also has an independent position in exposing news without intervention from other parties. This is indicated by the vice.com editor who chooses a diction that tends to have neither negative nor positive connotations. In addition, 26 direct quotes were found in 4 news articles. At the text level, events are delivered coherently and clearly. Media vice.com does not seem to have an agenda to provoke the public regarding this issue because the news tends to only provide information regarding the number of victims. The situation conveyed is related to events, individuals, groups, situations, and others in the text. The role of language in the text used by vice.com editors is to educate audiences to understand the realities that actually happen easily. At the discourse practice level, the news production system has freedom in the news production process and there is no intervention from the capital owner to directly affect the reporting of the case. At the level of sociocultural practice, media vice.com puts forward a controlled, safe and peaceful situation in the socio-political area of Surabaya.